Facts About Thiamin - R. Elaine Turner; Wendy J. Dahl (EDIS)
A lack of thiamin causes the disease beriberi. People with beriberi have difficulty standing, walking, and controlling their muscles. It’s very easy to get enough thiamin in the diet because it’s added to many processed grains. However, people who abuse alcohol or have a very poor diet may suffer from a thiamin deficiency. This revised 2-page fact sheet was written by R. Elaine Turner and Wendy J. Dahl, and published by the UF Department of Family, Youth and Community Sciences, April 2012.